Re-thinking Renaissance objects : design, function and meaning - Motture, Peta.; O'Malley, Michelle; Wiley InterScience (Online service) (Chichester : Wiley-Blackwell Pub., 2011)
"Re-thinking Renaissance objects considers key issues at the heart of current scholarly debate on Renaissance art and culture. Inspired by research that has developed from the redisplay of the outstanding Medieval and Renaissance collections at the Victoria and Albert Museum, the authors use the objects themselves as their starting point in their papers. The book explores and often challenges assumptions about the interconnection between sacred and secular belief, the problems inherent in making distinctions between 'artists' and 'artisans', and the various ways in which ideas were exchanged across media and cultural boundaries. This object-based approach has often helped revolutionize our thinking not only about individual pieces but also about the culture for which these works were created. The volume brings together V & A curators with other experts. The result is an impressive range of contributions which build on a wealth of existing scholarship in order to cast new light on the appearance, meaning, style and function of a collection of Renaissance artistic works"--
Front Matter -- Introduction / Peta Motture, Michelle O'malley -- Finding Fame: Painting and the Making of Careers in Renaissance Italy / Michelle O'Malley -- Set in Stone: Monumental Altar Frames in Renaissance Florence / Meghan Callahan, Donal Cooper -- Veit Stoss and the Origins of Collecting of Small-Scale Sculpture before 1500 / Norbert Jopek -- New Light on a Venetian Lantern at the V & A / Nick Humphrey, Martino Ferrari Bravo -- Rethinking the Petrucci Pavement / Elizabeth Miller, Alun Graves -- Dancing, Love and the b1(BBeautiful Gameb2(B: A New Interpretation of a Group of Fifteenth-Century b1(BGamingb2 (BBoxes / Paula Nuttall -- Sharing and Status: The Design and Function of a Sixteenth-Century Spanish Spice Stand in the Victoria and Albert Museum / Kirstin Kennedy -- Scattered Knives and Dismembered Song: Cutlery, Music and the Rituals of Dining / Flora Dennis -- Bibliography -- Index.s
Includes bibliographical references (pages 185-211) and index.
Print version record.
Keywords: Victoria and Albert Museum; Art, Renaissance; Art objects, Renaissance; Renaissance; Art objects, Renaissance; Art, Renaissance; Renaissance; Electronic books